A computational investigation on the substrate preference of ten-eleven-translocation 2 (TET2). Issue 6 (22nd January 2016) - Lu, Junyan; Hu, Lulu; Cheng, Jingdong; Fang, Dong; Wang, Chen; Yu, Kunqian; Jiang, Hualiang; Cui, Qiang; Xu, Yanhui; Luo, Cheng
Abstract : Computational modelling reveals the key step and atomic details for the substrate preference of TET2. Abstract : TET proteins iteratively convert 5-methylcytosine (5mC) into 5-hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC), and 5-carboxylcytosine (5caC) in a Fe(ii )/α-ketoglutarate-dependent manner. Our previous biochemical studies revealed that TET proteins are more active on 5mC than on 5hmC and 5fC. However, the source of the substrate preference of TET proteins still remains largely elusive. Here, we investigated the substrate binding and catalytic mechanisms of oxidation reactions mediated by TET2 on different substrates through computational approaches. In accordance with previous experimental reports, our computational results suggest that TET2 can bind to different substrates with comparable binding affinities and the hydrogen abstraction step in the catalytic cycle acts as the rate-limiting step. Further structural characterization of the intermediate structures revealed that the 5-substitution groups on 5hmC and 5fC adopt an unfavorable orientation for hydrogen abstraction, which leads to a higher energy barrier for 5hmC and 5fC (compared to 5mC) and thus a lower catalytic efficiency. In summary, our mechanical insights demonstrate that substrate preference is the intrinsic property of TET proteins and our theoretical calculation results can guide further dry-lab or wet-lab studies on the catalytic mechanism of TET proteins as well as other Fe(ii )/α-ketoglutarate (KG)-dependent dioxygenases.